Iron Deficiency n Pregnancy and its Impact on Mother and Fetus: A Systematic Review in Experimental Animal Models - Dinda Fachri; Ahmad Aulia Jusuf (Jurnal Sehat Indonesia (JUSINDO), 2026)
Iron deficiency is a common nutritional problem during pregnancy and is associated with maternal anemia and adverse pregnancy outcomes. Although clinical evidence in humans is widely available, mechanistic understanding of the impact of iron deficiency on the materno-fetal unit is still limited and requires support from experimental animal studies. This systematic review aims to comprehensively review the evidence from animal studies on the impact of iron deficiency during pregnancy on maternal health, placental function, and fetal development. Literature searches were conducted on PubMed, Scopus, and Web of Science databases for articles published between 2016–2025, following PRISMA guidelines. Studies that used models of pregnant animals with iron deficiency induction and reported maternal or fetal outcomes were included. Bias risk assessment was carried out using the SYRCLE tool. Seven studies met the inclusion criteria. Consistently, maternal iron deficiency causes anemia in the mother, placental dysfunction, increased oxidative stress, and inhibition of fetal growth and development. Evidence from animal models confirms the important role of iron in maintaining pregnancy health and provides a translationally relevant mechanistic basis for conditions in humans.